Beyond the Interface: Improved Pulmonary Surfactant-Assisted Drug Delivery through Surface-Associated Structures - Cristina García-Mouton; Mercedes Echaide; Luis A. Serrano; Guillermo Orellana; Fabrizio Salomone; Francesca Ricci; Barbara Pioselli; Davide Amidani; Antonio Cruz; Jesús Pérez-Gil (MDPI AG, 2023)
Pulmonary surfactant (PS) has been proposed as an efficient drug delivery vehicle for inhaled therapies. Its ability to adsorb and spread interfacially and transport different drugs associated with it has been studied mainly by different surface balance designs, typically interconnecting various compartments by interfacial paper bridges, mimicking in vitro the respiratory air-liquid interface. It has been demonstrated that only a monomolecular surface layer of PS/drug is able to cross this bridge. However, surfactant films are typically organized as multi-layered structures associated with the interface. The aim of this work was to explore the contribution of surface-associated structures to the spreading of PS and the transport of drugs. We have designed a novel vehiculization balance in which donor and recipient compartments are connected by a whole three-dimensional layer of liquid and not only by an interfacial bridge. By combining different surfactant formulations and liposomes with a fluorescent lipid dye and a model hydrophobic drug, budesonide (BUD), we observed that the use of the bridge significantly reduced the transfer of lipids and drug through the air-liquid interface in comparison to what can be spread through a fully open interfacial liquid layer. We conclude that three-dimensional structures connected to the surfactant interfacial film can provide an important additional contribution to interfacial delivery, as they are able to transport significant amounts of lipids and drugs during surfactant spreading.